Epithelial Remodelling in Myopia After Keratorefractive Lenticule Extraction - Maja Bohač; Ivan Gabrić; Sara Blazhevska; Mateja Jagić; Samuel Arba Mosquera (Ophthalmology and Therapy)
Abstract Introduction We analyzed longitudinal epithelial changes after the treatment of myopia with keratorefractive lenticule extraction (KLEx) and the zonal change in epithelial thickness up to 12 months after SmartSight for myopic astigmatism with the SCHWIND ATOS femtosecond laser. Methods We used anterior segment optical coherence tomography (AS-OCT) data and analyzed changes in the epithelium after treatment to ascertain how much epithelium hyperplasia occurred after KLEx. Data from 80 eyes treated with SmartSight, with a complete follow-up from postoperative day 1 (POD1) to 12 months postoperative, were used. The mean age of the patients was 29 ± 6 years with a mean spherical equivalent (SEQ) of − 4.72 ± 1.97 diopters (D) (− 1.25 to − 9.88 D) and a mean magnitude of refractive astigmatism of 0.90 ± 0.89 D. Preoperative central epithelial thickness was from 46 to 67 µm. Results Postoperative central epithelial thickness at 12-month follow-up was 3 ± 5 µm thicker than preoperatively. The other epithelial zones (nasal, superior, temporal, inferior) thickened by + 4 ± 4 µm. The epithelial change showed larger variability at POD1 and stabilized from 1 week onwards. Postoperatively, the change in epithelium was not different for the different zones, and it did not correlate with the achieved refractive changes for any zone at any time point. Conclusions The changes in epithelial thickness after KLEx for moderate myopia with SmartSight were minimal, indicating a low level of epithelial hyperplasia without resembling a regression-inducing lentoid. Findings suggest that KLEx with SCHWIND ATOS has a subtle impact on the epithelial thickness (with postoperative epithelium becoming slightly thicker). However, the differences remain below any clinical relevance.